Entre mondialisation et régionalisation, le projet euro-méditerranéen et ses enjeux agro-alimentaires : une lecture ricardienne - Regnault H. (The GATT and Mediterranean agricultural trade, 1997)
The free trade which is set up between the European Union and of the Eastern European countries of the south and of the Mediterranean relates to only the industrial products, and the recent agreements very slightly modify the conditions of the agricultural exchange. However, the success of the Euro-Mediterranean project supposes that are refitted the conditions of the agricultural exchange, as much in the north than in the south. The rise to manufacturing power of the south is braked (except for Turkey) by the impossibility of reaching food self-sufficiency and thus by the difficulty in resorting to an active management by the rate of exchange of external competitiveness.
Séminaire sur 'Le GATT et les Echanges Agricoles Méditerranéens', 1995/12/03-05, Chania (Greece)